Nucleolar protein PES1 is a marker of neuroblastoma outcome and is associated with neuroblastoma differentiation. Issue 3 (4th February 2015) - Nakaguro, Masato; Kiyonari, Shinichi; Kishida, Satoshi; Cao, Dongliang; Murakami‐Tonami, Yuko; Ichikawa, Hitoshi; Takeuchi, Ichiro; Nakamura, Shigeo; Kadomatsu, Kenji
Abstract : Neuroblastoma (NB) is a childhood malignant tumor that arises from precursor cells of the sympathetic nervous system. Spontaneous regression is a phenomenon unique to NBs and is caused by differentiation of tumor cells. PES1 is a multifunctional protein with roles in both neural development and ribosome biogenesis. Various kinds of models have revealed the significance of PES1 in neurodevelopment. However, the roles of PES1 in NB tumorigenesis and differentiation have remained unknown. Here we show that NB cases with MYCN amplification and clinically unfavorable stage (INSS stage 4) express higher levels of PES1 . High PES1 expression was associated with worse overall and relapse‐free survival. In NB cell lines, PES1 knockdown suppressed tumor cell growth and induced apoptosis. This growth inhibition was associated with the expression of NB differentiation markers. However, when the differentiation of NB cell lines was induced by the use of all‐trans retinoic acid, there was a corresponding decrease in PES1 expression. Pes1 expression of tumorspheres originated from MYCN transgenic mice also diminished after the induction of differentiation with growth factors. We also reanalyzed the distribution of PES1 in the nucleolus. PES1 was localized in the dense fibrillar component, but not in the granular component of nucleoli. After treatment with the DNA‐damaging agent camptothecin, this distribution was dramatically changed to diffuse nucleoplasmic. These data suggest that PES1 is a marker of NB outcome, that it regulates NB cell proliferation, and is associated with NB differentiation. Abstract : The nucleolar protein PES1 is highly expressed in clinically unfavorable neuroblastoma cases. PES1 expression is closely associated with differentiation condition of neuroblastoma cell lines or tumor spheres. PES1 is distributed in dense fibrillar component in the nucleoli and the distribution radically changes after DNA damage.